Effectiveness of mind mapping technique in information retrieval among medical college students in Puducherry-A pilot study - Madhanraj Kalyanasundaram; Sherin Billy Abraham; Divija Ramachandran; Venkatachalam Jayaseelan; Joy Bazroy; Zile Singh; Anil Jacob Purty (Wolters Kluwer Medknow Publications, 2017)
Background: The traditional teaching learning methods involve a one way process of transmission of knowledge leaving the students lacking behind in creative abilities. Medical schools need to change their teaching strategies to keep the interest of students and empower them for future self- learning and critical thinking. Objective: To assess the impact of mind mapping technique in information retrieval among medical college students in Puducherry. Methods: A pilot study was conducted using experimental study design among sixth semester MBBS students (n = 64) at a medical college in Puducherry, India. One group (n = 32) followed the text reading method and another group (n = 32) followed the mind mapping technique to learn the same passage given to them. The knowledge about the topic was assessed using a pre designed questionnaire at baseline, day 0 and day 7. The knowledge gain is the primary outcome variable and is compared between two groups. The feedback regarding the teaching methods was obtained from the participants. Results: Mean knowledge score in the text group was lesser than the mind map group at baseline (2.6 Vs 3.5; p = 0.08). On Day 0, the mean score in text group was slightly lesser than the mind map group (8.7 Vs 9.0; p = 0.26). On Day 7, the mean score in mind map group is significantly more than the text group (8.9 Vs 8.5; p = 0.03). Conclusion: The mind mapping technique is an innovative and effective method in remembering things better than the routine way of reading texts.